Queer Eye: The Urgency Of Self-Representation In The Study Of Coming-In Processes And Self-Acceptance Of Nonbinary Transgender Individuals - Ummanabiegh Ismail Jalla; Irwan Martua Hidayana (Publikasi Indonesia, 2023)
The non-binary Trans identity is one of the marginal identities beginning to be recognized worldwide. Research articles and academic resources available on non-binarynonbinary Trans identities write about various aspects of the internal and external processes of self-acceptance of non-binary Trans individuals, including gender dysphoria, transphobic internalization, gender deconstruction, and environmental cisnormativity, with various concepts and theories that raise disparities and unanswered questions. In this literature review, the authors collected and critically analyzed 16 documents to fill theoretical gaps regarding research into non-binary Trans identities. It was found that research on non-binary Trans identities has gained popularity in the past decade. However, of the available sources of research articles, few studies have used queer theory to analyze experiences of non-binarynonbinary Trans identities